Artistic Freedom against Moral Responsibilities: An Appraisal of Aesthetics against Ethics - Bhattarai, Gaurav (KMC Research Journal, 2018)
How the hate speech should be separated from the free speech and why the blasphemous laws should be banned to shield free thought and freedom of expression from any danger or damage? This article examines the argument that whether blasphemous art should be publicly displayed, and if yes, in what manner artist are free and to what extent they should be responsible while exercising their artistic freedom. The write-up argues against those who say blasphemy is an offence, an attack on religion and sacred, to aver that blasphemy shouldn’t be understood merely on the moral and ethical lines, but through the contextual and philosophical understandings of the issue. Particularly, this write-up criticizes the blasphemy laws, including fatwas and death threats issued against two writers–Salman Rushdie and Taslima Nasrin. Finally, this paper discusses how the notion of blasphemy itself is the product of misunderstanding and misreading the free speech as the hate speech. The article concludes that the line between aesthetics and ethics, between art and religion, should be drawn only by the rationalistic judgment of the contextual issues and for that artist’s intention should be realized at first, before colligating it with the religious matters, ethical issues and falsely apprehending freedom of thought as a sacrilege and profanation.